Economic crimes in oil and gas sector in law of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
In this article, the author analyzes the main economic crimes in the oil and gas sector. By offering timelyimprovements to the criminal legislation of the Republic of Kazakhstan for the prevention and control ofeconomic crime in the oil and gas industry of Kazakhstan.Keywords: economic crimes, oil and gas, fighting, law, hydrocarbons.